The Rise of Political Warfare: Russian New Way of War against the West and the Western Counteractions - Hasan Suzen (Department of Government Studies Universitas Muhammadiyah Makassar, 2018)
Since the outbreak of the Ukraine crisis, the world has observed a comprehensive Russian political warfare, which has had destabilising consequences and as well as wide-ranging implications for international security, in particular for Europe. On the other hand, in the aftermath of the Cold War, the West mostly focus on public diplomacy and strategic communication rather than political warfare. This change creates a gap in all features of political warfare and makes the West weak to political warfare waged by particularly one-man ruled states. In this respect, firstly, I will define political warfare in the continuum of peace and war. Then, I will develop a new conceptual framework which provides an interdisciplinary approach to understand the specifics of political warfare against the West and its counteractions. To explore how and why the West has failed in countering and undermining political warfare employed by especially one-man ruled states, I will explain the origin and evolution of Russian political warfare and particularly highlight the Ukraine Crisis as a turning point of Russian political warfare which has been evolving since the 1900s. Finally, I will propose ways and means to explain how to counter political warfare using hybrid tactics in the future.